Feasibility assessment of expansion options for a fish feed factory in Iceland - Ágúst Freyr Dansson 1988- (2015)
Fish farming in Iceland has been growing steadily since 2008. With better farming technologies it is becoming increasingly profitable and demand for feed is increasing. Domestic fish feed factories will not be capable of producing enough feed to supply the Icelandic market in the coming years if this trend continues. Old equipment also prevents optimal fat content in feed production. A new factory or upgrade is necessary for Laxá to stay competitive. This paper presents a feasibility model for comparison of a new 50.000 ton fish feed factory versus upgrading existing facilities at Laxá to supply increased demand. Risk analysis and inventory optimization are also presented for both options and optimal location is determined for a new factory. Both investment options are feasible at the end of the planning horizon. A new factory has 18% IRR and NPV of 725 M ISK. A factory upgrade returns 25% IRR and NPV of 231 M ISK. With no clear favorite the selection could ultimately depend on the risk attitude of Laxá executives and project investors. Fiskeldi á Íslandi hefur aukist jafnt og þétt síðan 2008. Tækniframfarir hafa leitt til þess að fiskeldi er orðið arðbærara en áður og því er horft í auknum mæli til þess. Samhliða auknu eldi þarf aukið magn fóðurs. Fiskifóðurs verksmiðjur innanlands munu ekki anna eftirspurn ef þessi þróun heldur áfram. Gamall tækjabúnaður gerir Laxá ekki kleift að framleiða fóður með ákjósanlegu fitumagni. Því er endurnýjun búnaðar eða ný verksmiðja nauðsynleg til að halda samkeppnishæfni. Framkvæmd er arðsemisgreining á 2 valmöguleikum fyrir Laxá. Bygging nýrrar 50.000 tonna verksmiðju eða endurnýjun búnaðar við núverandi verksmiðju fyrirtækisins. Áhættugreining og bestun á birgðahaldi fyrir báða valmöguleika er framkvæmd ásamt bestun á staðsetningu nýrrar verksmiðju á Vestfjörðum. Báðir fjárfestingar möguleikar eru arðbærir í lok áætlanargerðar. Núvirði nýrrar verksmiðju er 725 M ISK og innri vextir 18%. Endurnýjun nýrrar verksmiðju skilar núvirði upp á 231 M ISK og 25% innri vöxtum. Þar ...